Răspuns :
[(a : 3 + 7 ) × 6 ] - 48 = 60
[( a : 3 + 7 ) × 6 ] = 60 + 48
( a : 3 + 7 ) × 6 = 108
( a : 3 + 7) = 108 : 6
( a : 3 + 7 ) = 18
a : 3 + 7 = 18
a : 3 = 18 - 7
a : 3 = 11
a = 11 × 3
a = 33
[( a : 3 + 7 ) × 6 ] = 60 + 48
( a : 3 + 7 ) × 6 = 108
( a : 3 + 7) = 108 : 6
( a : 3 + 7 ) = 18
a : 3 + 7 = 18
a : 3 = 18 - 7
a : 3 = 11
a = 11 × 3
a = 33
O sa notm cu X numarul la care te ai Gandit atunci
(X:3+7)×6-48=60
(X:3+7)×6=60+48
(X:3+7)×6=108
X:3+7=108:6
X:3+7=18
X:3=18-7
X:3=11
X=11×3
X=33
(X:3+7)×6-48=60
(X:3+7)×6=60+48
(X:3+7)×6=108
X:3+7=108:6
X:3+7=18
X:3=18-7
X:3=11
X=11×3
X=33